2019
DOI: 10.1016/j.jped.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with objectively measured total sedentary time and screen time in children aged 9–11 years

Abstract: Several associated factors were identified in the association between total sedentary time and screen time in children; however, only the healthy dietary pattern was common between sedentary time and screen time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
8
0
2
Order By: Relevance
“…25,26 In both sexes, the number of steps/day was positively associated to MVPA, and negatively, to ST. Although treated as independent variables, there is a negative relationship between PA and ST. 27 These results suggest that both ST and steps/ day can be considered when strategic planning and program implementation are prepared to reduce risks in children.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…25,26 In both sexes, the number of steps/day was positively associated to MVPA, and negatively, to ST. Although treated as independent variables, there is a negative relationship between PA and ST. 27 These results suggest that both ST and steps/ day can be considered when strategic planning and program implementation are prepared to reduce risks in children.…”
Section: Discussionmentioning
confidence: 91%
“…The study's transversal design does not allow establishing a cause and effect relationship; sample is not representative; São Caetano do Sul City has a high HDI, besides PA and healthy eating policy and practice programs that help decrease ST and obesity of children in the city. 12,17,27 In contrast, the use of an accelerometer as an instrument for objective measurement of the number of steps, in addition to considering the vast amount of lifestyle, and home and school environment variables, were certainly study's strengths.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of differences may be due to SB being self-reported, as opposed to more objective data such as from an accelerometer [33,37]. Another possible explanation of the lack of sex differences might be the low sample size in the Special Eurobarometers as previous studies reported that girls and boys engage differently in sedentary activities, with boys reporting more TV or computer games, and girls reporting more time in communication or social media activities [17,18]. Thus, further studies are needed to verify or reject the findings reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside this, the electronic revolution has transformed people's movement patterns, significantly increasing the amount of daily time in front of the screen (e.g., televisions, computers, smartphones, etc.) [17,18], and by sex, girls usually report a slightly higher prevalence of SB than boys [3]. Furthermore, there seem to be sex differences in how SB is accumulated, with boys reporting more screen time (televisions or computer games) and girls spending more time in communication-based SB (surfing the internet, texting, talking on the phone) [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation